Lazada, Shopee atau Tokopedia? Sebuah Preferensi Lokapasar oleh Mahasiswa Pekerja di Area Tangerang Raya - Chandra Fitra Arifianto; Yuli Endah Pratiwi (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2021)
This research was conducted to see the preferences of studen-workers in the Greater Tangerang area in determining 3 marketplaces (marketplaces), namely: Lazada, Shopee and Tokopedia, which they considered better. The literature review in this study was sourced from Svobodová and Rajchlová (2020) regarding the identification of online buying behavior which consists of 13 components, namely: reviews and complaints, certification and security, advertising and communication, product prices, websites, organizational factors, product descriptions, payment methods, store chains, transportation, and discounts. This is a descriptive survey study that uses 55 student-workers as respondents in answering the questionnaire submitted by the researcher. Simple percentages were used for data analysis. The research findings show that Tokopedia has the highest average respondent's answer assessment. So it can be assumed that Tokopedia is superior in fulfilling the 13 components to identify online buying behavior. In addition, it was also revealed that the components of reviews and complaints as well as transportation are priorities for consumers in making online purchases.